Influence of a Brazilian sewage outfall on the toxicity and contamination of adjacent sediments - Abessa, DMS; Carr, R. S.; Rachid, BRF; Sousa, ECPM; Hortellani, M. A.; Sarkis, J. E. (Elsevier B.V., 2005)
The submarine sewage outfall of Santos (SSOS) is situated in the Santos Bay (São Paulo, Brazil) and is potentially a significant source of contaminants to the adjacent marine ecosystem. The present study aimed to assess the influence of SSOS on the sediment toxicity and contamination at Santos Bay. At the disposal site, sediments tended to be finer, organically richer and exhibited higher levels of surfactants and metals, sometimes exceeding the Threshold Effect Level values. The SSOS influence was more evident toward the East, where the sediments exhibited higher levels of TOC, total S and metals during the summer 2000 sampling campaign. Sediment toxicity to amphipods was consistently detected in four of the five stations studied. Amphipod survival tended to correlate negatively to Hg, total N and % mud. This work provides evidence that the SSOS discharge affects the quality of sediments from Santos Bay, and that control procedures are warranted. (c) 2005 Elsevier Ltd. All rights reserved.
Keywords: sewage; sediments; toxicity; marine pollution; Santos; sewage outfall